IMPLEMENTATION SURVEY OF A QUALITY MANAGEMENT SYSTEM ACCORDING TO STANDARD ISO / IEC 17025 : 2005 – IN THE PULP AND PAPER LABORATORY UNESP- ITAPEVA- BRAZIL. - BATAGIN, Bruno; PRATES, Glaucia Aparecida; CAMPOS, Cristiane Inácio de; GOVEIA, Danielle (Revista Brasileira de Engenharia de Biossistemas, 2013)
The aim of this study is to perform a situational analysis of the Laboratory of pulp and paper-UNESP ITAPEVA for conducting proposal the accreditation according to ISO / IEC 17025:2005. The ISO / IEC 17025 establishes the criteria for those laboratories wishing to demonstrate their technical competence, which have an effective quality system and are able to generate technically valid results, establishing a single international standard for certifying the competence of laboratories to carry tests and / or calibrations, including sampling. The case study was conducted on laboratory Pulp and Paper Universidade Estadual Paulista (UNESP), campus Itapeva, where we compared the views of the technician responsible for the laboratory and a regular user. The generated conclusion is that the laboratory is unable to initiate an accreditation process, because it fails the requirements such as quality manual, register of subcontractors, research of customer satisfaction, schedule of internal audits, schedule for completion of critical analysis, profile of the functions required, functions current description, documentation of technical requirements for accommodation and environmental conditions, calibration programs, equipment calibration program, programs calibration standards and reports and / or certificate of test and / or calibration, that are in accordance with ISO / IEC 17025:2005, beyond that there is not the possibility to develop and implement a quality system without the commitment of everyone involved, regardless of the functional hierarchy.